Adaptation Of Climate Change In Cimangeunteung Village Lebak District In The Framework Of Improving Regional Resilience - Clara Bilqis Florissa; Adi Subiyanto; Christine Sri Marnani; Pujo Widodo; Herlina Juni Risma Saragih (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Climate change causes an increase in the incidence of natural disasters which, if not handled seriously, will threaten regional resilience. Lebak Regency is one of the areas in Indonesia which is not spared from the impacts of climate change. In 2019 there were many drought disasters in Lebak Regency, but there was one village that was not affected by drought, namely Cimangeunteung Village. This becomes interesting for further research by researchers. The data was taken based on the results of interviews, observations, and documents using the interactive model qualitative research methods belonging to Miles, Hubermen, and Saldana (2014). The purpose of this study is to determine the impact of climate change on potential disasters in Lebak Regency and to analyze the adaptation efforts made by the people of Cimangeunteung Village. The results of this study are 1) Climate change has caused the number of disasters due to climate change such as floods, droughts and landslides to increase in Lebak Regency. 2) The implementation of fostering climate change adaptation in Cimangeunteung Village is carried out through the activity of creating a waste bank; construction of walls of spring wells; and the formation of the Women Farmers Group. Climate change adaptation activities in Cimangeunteung Village have been well implemented and have succeeded in increasing public awareness in caring for the environment. Routine monitoring by the Lebak local government of Cimangeunteung Village is still being carried out to date.